ANALISIS FAKTOR NORMA SUBJEKTIF TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR PADA KANTOR BERSAMA SAMSAT KABUPATEN PINRANG - Gusti Gusti; Mahmud Nuhung; abd Salam (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2019)
The purpose of this study was to determine the effect of subjective norms on motor vehicle taxpayer compliance. the type of research used in this study is quantitative descriptive analysis.The analysis method used in this research is inductive, deductive, and cumulative analysis methods. Based on the results of an analysis of the influence of subjective norms, several factors were found to be factors for motor vehicle taxpayer compliance.From the results of the analysis of the influence of subjective norms on taxpayer compliance based on measurements using the cumulative frequency of subjective norms shows that the items on the questionnaire have an effect on taxpayer compliance, which is a factor of taxpayer compliance is also caused by good service quality, because it has fulfill several dimensions of service. So that in this study subjective norms are stated to have a positive effect on taxpayer compliance.